ALAT PRAKTIKUM FISIKA GERAK JATUH BEBAS MENGGUNAKAN ATMEGA32 - , ANDHI ALIEM WICAKSANA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Free fall motion is an object motion that falling from a height without initial velocity and affected by gravity. Free fall motion usually shown by uniformly accelerated motion in a vertical line and that falling objects are not pushed by force but fall by itself. In this final has made a free fall motion system to measure the value of kinetic energy, potential and mechanical energy by using atmega 32 as central data processor and ultrasonic sensor used as the height detector. This system is packaged attractively with LCD display, physical shape of the device shaped as high as 1.1 meters, so students can see the result of energies from free fall motion on the LCD. From the experiment that have been done, which the energy value each the variation result of the height and the mass object that used. Gravity which used is also different.